Prevalence, Incidence, Risk and Protective Factors of Amnestic Mild Cognitive Impairment in the Elderly in Shanghai - Wang, Tao; Xiao, Shifu; Chen, Kewei; Yang, Cece; Dong, Shuhui; Cheng, Yan; Li, Xia; Wang, Jinghua; Zhu, Minjie; Yang, Fuzhong; Li, Guanjun; Su, Ning; et al. (Current Alzheimer Research, 2017)
Background: Amnestic MCI (aMCI) has notably increased in Shanghai, China. Objective: The study was designed to estimate the prevalence and incidence rates of aMCI and to determine the risk and protective factors for aMCI among persons ≥ 60 years-old and ≥ 70 years-old in Shanghai communities, respectively. Method: We carried out this 1-year longitudinal study to survey a random sample of 1,302 individuals ≥ 60 years-old, to collect baseline and follow-up data about lifestyle through self-reports, and vascular and comorbid conditions from medical records and a physical examination. We also analyzed a subgroup of individuals ≥ 70 years-old. Results: The prevalence rate of aMCI in persons ≥ 60 years-old was 22.3%, and the incidence rate (per 1,000 person-years) was 96.9. Being female was a risk factor for aMCI; protective factors included smoking, drinking tea, engaging in intellectual work before retirement, social activities and hobbies, regular reading habits, and surfing the internet. The prevalence rate of aMCI in persons ≥ 70 years was 30.3%, and the incidence rate was 145.6. Smoking, drinking tea, and surfing the internet were not protective factors for this age group (≥ 70 years). Conclusion: The present study indicates that aMCI is a considerable health problem in Shanghai. Preventive strategies for aMCI are needed to enhance lifestyle factors that promote brain activity.
Keywords: risk factor